Narratives in conflict and the limits on the interpreter’s agency: A case study from the UN Peacekeeping mission in Lebanon - Moreno-Bello, Yolanda (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This article presents a socio-linguistic analysis of interpreting in conflict zones and paints a picture of the limits on the interpreter’s agency when working in the field. It focuses on the interpreter’s behaviour towards cultural and linguistic barriers in communication between foreign military personnel and the civilian population in Lebanon. The aim is to analyse the level of agency that the interpreter has when working in a military deployment, taking into account the context and the narrative features that require mediation. Data were gathered through interviews with interpreters in Lebanon and analysed by applying narrative theory. Knowing and appreciating both the theoretical context and the linguistic and cultural barriers identified through the analysis are fundamental to understanding the difficult role that the interpreter-mediator plays in conflict settings and to reflecting on interpreter training that is appropriate to this context.